"Women's Resistance against Patriarchal Culture in the novella Al-Lawn Al-Akhar by Ihsan Abdul Quddus" - Nurul Istiqomah; Evelin Giovani; Survey Sijabat (Musamus Journal of Language and Literature, 2023)
The aim of this research is to describe the resistance exhibited by female characters towards their husbands and families, as demonstrated through open and covert forms of resistance in the novella "Al-Lawn Al-Akhar." The data collection technique employed in this study is literature review. The data analysis technique used is descriptive analysis. The research adopts a sociological approach to literature with James C. Scott's theory of resistance. The primary data source utilized is the novella "Al-Lawn Al-Akhar" by Ihsan Abdul Quddus. The findings of this research indicate the presence of two forms of resistance in the novella "Al-Lawn Al-Akhar" by Ihsan Abdul Quddus: open resistance and covert resistance. 1) Public resistance is demonstrated by female characters in the novella through acts of rebellion, contradiction, anger, and threats expressed with a raised voice and visible facial expressions. This form of resistance is adopted by female characters who feel they are being treated unfairly or denied justice, prompting them to resist in order to defend themselves and seek their rights or justice. 2) Hidden resistance is practiced by the female character within the novella. It is manifested through silent grumbling and cursing within their hearts, behavior that reflects disapproval, silence, and concealed tears not shown to others.